Transformasi Karakter Siswa: Peran Sekolah Sisan Ngaji dalam Pendidikan Berbasis Nilai - Tsani, Bilal Ahmad; Ali, Mohamad (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to describe the implementation of the Sekolah Sisan Ngaji (SSN) program in building students’ character at SMP Muhammadiyah 5 Randulatung. The study employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with the principal, religious education teachers, and students, and program documentation. The findings indicate that the SSN program is conducted regularly after formal learning activities, with materials focusing on the habituation of worship, strengthening of noble moral values, and spiritual development of students. This program does not only emphasize religious cognitive aspects but also internalizes character values such as discipline, responsibility, and honesty in students’ daily lives. Challenges in implementing the SSN program include students’ lack of motivation, limited time, and minimal parental involvement. However, the school has addressed some of these challenges through creative learning methods, strengthened collaboration with parents, and teacher training. The findings confirm that SSN positively contributes to students’ character development when implemented consistently and supported by all stakeholders. The study recommends regular program evaluation and enhancing teachers’ capacity to guide students’ holistic character development. Implication: The results of this study imply that character-building programs based on religious activities such as SSN can serve as a model for strengthening character education in other schools, especially within the context of Islamic teaching. Implementing similar programs requires institutional support, active parental involvement, and teacher capacity-building to ensure that character education can be carried out effectively, comprehensively, and sustainably.